THE RELATIONSHIP BETWEEN SOCIAL SUPPORT AND RESILIENCE AND SUBJECTIVE STUDENT WELL-BEING: A SYSTEMATIC REVIEW OF LITERATURE - Sheren Wifa Siltata; Herdi Herdi; Karsih Karsih (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to examine the relationship between social support and resilience with students’ subjective well-being through a Systematic Literature Review (SLR) approach. The review analyzed three peer-reviewed articles published within the last five years that met specific inclusion criteria. Findings reveal that social support from family, peers, and the academic environment plays a crucial role in enhancing both resilience and students’ subjective well-being. Resilience acts as a mediator that strengthens the effect of social support on well-being, showing that highly resilient individuals are better equipped to cope with stress and maintain psychological health. The reviewed studies consistently demonstrate that social support and resilience significantly contribute to life satisfaction, positive emotions, and students' mental well-being. These findings highlight the importance of developing social support-based interventions and resilience training as strategic efforts to enhance adolescents' subjective well-being within educational settings.